Estimation of Non‐Metallic Inclusions in Industrial Ni Based Alloys 825. Issue 4 (2nd March 2017) - Kellner, Hans E. O.; Karasev, Andrey V.; Sundqvist, Olle; Memarpour, Arashk; Jönsson, Pär G.
Abstract : It is well known that inclusions affect the properties of the steel and other alloys. The importance of understanding the behavior of the inclusions during production can never be overstated. This study has examined the main types of big size (>10 μm) inclusions that exist in Ni‐based Alloy at the end of ladle treatment and after casting during industrial production of Ni based Alloys 825. Sources, mechanisms of formation and behavior of different type large size inclusions in Alloy 825 are discussed based on 2 and 3D investigations of inclusion characteristics (such as, morphology, composition, size, and number) and thermodynamic considerations. The large size inclusions found can be divided in spherical (Type I and II) inclusions and in clusters (Type III–V). Type I‐A inclusions (Al2 O3 –CaO–MgO) originate from the slag. Type I‐B inclusions and Type II inclusions consist of CaO–Al2 O3 –MgO and Al2 O3 –TiO2 –CaO, respectively. Both types originate from the FeTi70R alloy. Type III clusters (Al2 O3 –MgO–CaO) are formed during an Al deoxidation of the Ni‐based alloy. Type IV clusters (Al2 O3 –TiO2 –CaO) formed from small inclusions, which are precipitated in local zones which contain high Ti and Al levels. These clusters are transformed to Type III clusters over time in the ladle. Finally, Type V clusters are typical TiN clusters. Abstract : Investigations regarding large size (>10 µm) inclusions are performed for Ni based Alloy 825 to understand what inclusions exist and where they come from. This is done at the end of the ladle treatment and after casting for comparison. Both 2D and 3D investigations are done to better understand the inclusions.